Taxing Expats - Instrumental versus Expressive Voting Compared - Charles Beat Blankart; Simon Margraf (Swiss Journal of Economics and Statistics, 2011)
It is common knowledge that mobile individuals are difficult to tax. Governments accommodate these difficulties by granting special tax reductions to mobile individuals as it is expedient to get some tax revenue from these individuals rather than to lose them as tax payers completely. Taxing according to expediency is, however, criticized by ordinary tax payers who claim that the basic principles of tax equity are consequently violated. Therefore governments have to solve a difficult trade off between the two goals in order to survive. The variables entering in this optimization process remain disguised in the normal case of a representative democracy. In a direct democracy, however, the trade-off between tax expediency and tax equity principles is revealed by voters.In this paper we distinguish between situations where voters vote instrumentally in favour of tax expediency and where voters vote expressively in favour of equity principles. A popular vote in the canton of Zurich of 2009 serves as a natural experiment for testing the instrumental versus expressive voter hypotheses. We find that instrumental voting prevails in small rural municipalities and expressive voting in larger cities. As expressive voters are in majority in the canton, they exert a cross border externality by imposing their will on the majority decisions of the smaller municipalities. This observation may be of a particular importance when, on the federal level, expressive urban voters may impose their will on the voters of rural cantons voting instrumentally.
Keywords: D72; H24; H71; 330; Political Economics of Taxation